Detection of magnetic fields in chemically peculiar stars observed with the K2 space mission. Issue 2 (5th May 2018) - Buysschaert, B; Neiner, C; Martin, A J; Aerts, C; Bowman, D M; Oksala, M E; Van Reeth, T
ABSTRACT: We report the results of an observational study aimed at searching for magnetic pulsating hot stars suitable for magneto-asteroseismology. A sample of 16 chemically peculiar stars was selected and analysed using both high-resolution spectropolarimetry with ESPaDOnS and K2 high-precision space photometry. For all stars, we derive the effective temperature, surface gravity, rotational, and non-rotational line broadening from our spectropolarimetric data. High-quality K2 light curves were obtained for 13 of the 16 stars andrevealed rotational modulation, providing accurate rotation periods. Two stars show evidence for roAp pulsations, and one star shows signatures of internal gravity waves or unresolved g-mode pulsations. We confirm the presence of a large-scale magnetic field for 11 of the studied stars, of which nine are first detections. Further, we report one marginal detection and four non-detections. Two of the stars with a non-detected magnetic field show rotational modulation due to surface abundance inhomogeneities in the K2 light curve, and we confirm that the other two are chemically peculiar. Thus, these five stars likely host a weak (undetected) large-scale magnetic field.